Formulasi dan Aktivitas Gel yang Mengandung Nanopartikel Ekstrak Temulawak sebagai Antiacne - Anastasya Anastasya; Deni Rahmat; Anarisa Budiati (JURNAL ILMU KEFARMASIAN INDONESIA, 2020)
Javanese turmeric is one of the Indonesia’s authentic plant that has many beneﬁts, antimicrobial eﬀect is one of them. Curcuminoid and xanthorrhizol contents are responsible for it's antimicrobial activity. Acne vulgaris is one of skin’s disorder that caused by bacteria, the major cause is Propionibacterium acnes. This study aimed to compare antimicrobial activity diﬀerence between nanoparticle and extract gel. Javanese turmeric was extracted and then formulated into nanoparticles. Javanese turmeric extract and it's nanoparticles were then formulated in gel preparation. Gel preparations were evaluated physically (organoleptic, homogeinity, spreadibility, and viscosity and rheology), chemically (pH value), and tested for their antimicrobial activity. Gel evaluations showed that both formula (nanoparticle and extract gel formula) did not show any discoloration and still homogeny. Extract gel formula had viscosity about 1540–1600 Ps, while nano extract gel had viscosity in the range of 487.63–501.01Ps. Extract gel formula had spreadability in the range of 51.75-53.35 mm, while nano extract gel has viscosity in the range of 65.125-72.75 mm. Extract gel formula had pH value in the range of 5.98–6.02, while nano extract gel had pH value in the range of 5.88–5.93. Extract gel formula has inhibition zone in the range of 10.0 mm–10.3 mm, while nanoextract gel has inhibition zone in the range of 13.0 mm–13.4 mm. Based on statistical paired sample t-test analysis, nano extract gel formula was signiﬁ cantly diﬀerent from extract gel formula in antimicrobial activity.